Proficiency in Using Level Cue for Sound Localization Is Related to the Auditory Cortical Structure in Patients With Single-Sided Deafness - Kim, Ja Hee; Shim, Leeseul; Bahng, Junghwa; Lee, Hyo-Jeong (Frontiers in Neuroscience, 2021)
Spatial hearing, which largely relies on binaural time/level cues, is a challenge for patients with asymmetric hearing. The degree of the deficit is largely variable, and better sound localization performance is frequently reported. Studies on the compensatory mechanism revealed that monaural level cues and monoaural spectral cues contribute to variable behavior in those patients who lack binaural spatial cues. However, changes in the monaural level cues have not yet been separately investigated. In this study, the use of the level cue in sound localization was measured using stimuli of 1 kHz at a fixed level in patients with single-sided deafness (SSD), the most severe form of asymmetric hearing. The mean absolute error (MAE) was calculated and related to the duration/age onset of SSD. To elucidate the biological correlate of this variable behavior, sound localization ability was compared with the cortical volume of the parcellated auditory cortex. In both SSD patients (n = 26) and normal controls with one ear acutely plugged (n = 23), localization performance was best on the intact ear side; otherwise, there was wide interindividual variability. In the SSD group, the MAE on the intact ear side was worse than that of the acutely plugged controls, and it deteriorated with longer duration/younger age at SSD onset. On the impaired ear side, MAE improved with longer duration/younger age at SSD onset. Performance asymmetry across lateral hemifields decreased in the SSD group, and the maximum decrease was observed with the most extended duration/youngest age at SSD onset. The decreased functional asymmetry in patients with right SSD was related to greater cortical volumes in the right posterior superior temporal gyrus and the left planum temporale, which are typically involved in auditory spatial processing. The study results suggest that structural plasticity in the auditory cortex is related to behavioral changes in sound localization when utilizing monaural level cues in patients with SSD.